Crecimiento inclusivo, desarrollllo local y comunicación: Del discurso a la práctica - Carrillo, Sandra (2016)
It has been demonstrated that economic growth is a required condition but not enough to reduce poverty and inequality, which are obstacles to the full development of every society. As a result, different perspectives have emerged to challenge the current measurement of development, based on gross domestic product (GDP). Inclusive growth is a new approach that offers a combination of increased prosperity and greater equity. This article argues that the perspective of inclusive growth can draw on strategies implemented as local economic development (LED), and that communication for development is a significant alternative to move from discourse to implementation of endogenous processes. This analysis is based on the reality of countries rich in natural resources, particularly Peru, where economic growth and reduction of monetary poverty have been considerable, while the quality of life of its population has not necessarily improved in the same proportion. Communication for development plays a key role in the context of inclusive growth agenda in Peru, as it promotes the empowerment and coordination between public and private actors.